Effects of soil vegetation on shallow slope instability. Issue 3 (1st May 2015) - Cecconi, Manuela; Pane, Vincenzo; Napoli, Patrizio
Abstract : Slope vegetation is currently finding wide applications all over the world to mitigate erosive phenomena and improve slope stability. A natural technology for slope protection has been recently developed in Italy; this uses only natural perennial grass plants with thin, deep roots with high tensile strength. The technology appears promising with regard to shallow slope instability because both the mechanical and hydrological effects of such a kind of soil vegetation may enhance the equilibrium conditions in the superficial (1 ÷ 2 m) portion of the slope. This short communication deals primarily with the positive mechanical effect of the roots in a simple infinite slope stability problem. With regard to the hydrological effects of the roots, some preliminary results of a numerical analysis are presented; in particular, for the specific case study herein discussed, such analysis allows highlighting the different roles played by deep roots permeating a cohesionless soil.